Axiology of Space as a Component of the Modern Theory of Land Use Organization: Value Regimes, Institutions, and Instruments of Spatial Order - Martyn А.; Hunko, L.; Poltavets, A. (Land Management, Cadastre and Land Monitoring, 2026)
The novelty of this study lies in the comprehensive comparison of the two systems in terms of legal effectiveness, digitalization, and protection of property rights. The conclusions of the research can be used to improve the Ukrainian real estate registration model, integrate cadastral and registration processes, and enhance legal certainty, bringing it closer to European standards. The article reveals the axiology of space as a component of the modern theory of land management and as a methodological response to the widespread reduction of space to geometric extension or a resource. It is substantiated that land management decisions always have not only a metric and resource-related dimension, but also a value-normative dimension, since space is a bearer of economic, environmental, social, cultural, security-related, and legal meanings and an arena of their conflicts. The purpose of the study is to conceptualize the theoretical and methodological foundations of the axiology of space in land management, to describe the mechanism of transition from values to institutional and design decisions, and to build a conceptual model of “value regimes of space.” The methodological basis consists of a systematized review of relevant scientific and framework sources, a conceptual analysis of basic categories (value, regime, legitimacy, admissibility), and a typologization of regimes supplemented by operationalization through indicator-metrics suitable for land management analytics. A definition of a value regime is proposed as a stable configuration of priorities закрепленої in institutions and practices, and a typology of regimes is presented (utilitarian-economic; environmental-protective; socially just; cultural-identification; security-related/risk-oriented; legal/procedural) with applied manifestations in land management and a set of quantitative metrics. The problem of commensurability is considered separately: it is shown that the use of a single metric for optimization models is possible only with a transparent distinction between threshold constraints (inadmissibility) and compromise criteria (weighted optimization), which opens the possibility of correct use of mathematical methods and geographic information system modeling in the design of spatial decisions. The practical value of the article lies in forming a categorically and instrumentally coherent framework for substantiating land management decisions as management of the value of space and for increasing the transparency of reconciling “benefit / irreplaceability,” “private interest / common good,” “local / general.” Received: 19.02.2026; Accepted: 03.03.2026;